Analisis Faktor Minat Kunjungan Siswa ke Perpustakaan SMAN 24 Bandung: Studi Kuantitatif - Permatasari, Suci; Firdza Rahmania Zahra; Rizkia Ramadhani; Mohamad Alfan Zidan; Wisnu Uriawan; Falih Ijal Septian (Education Library, 2026)
Student interest in visiting the school library is an important indicator in supporting a culture of literacy and the effectiveness of the library's function as a learning resource center. At SMAN 24 Bandung, the low level of visits indicates certain factors that influence student behavior in utilizing library services, so it needs to be analyzed systematically. This study used a descriptive quantitative method by distributing closed questionnaires to 117 students selected through a simple random sampling technique. The instrument was tested using validity and reliability tests before being used for data collection. Data were analyzed using descriptive statistics, Pearson correlation, and ANOVA tests using SPSS to determine the relationship between variables and differences in interest in visiting by grade group. Data were analyzed using descriptive statistics, Pearson correlation, and ANOVA tests using SPSS to determine the relationship between variables and differences in interest in visiting by grade group. The findings showed that collection quality, librarian services, facilities, and school support contributed to student interest in visiting. The ANOVA results indicated significant differences between levels, with 10th-grade students having the highest interest in visiting. In addition, there was a positive relationship between reading interest and the intensity of student visits. Student interest in visiting is formed through a combination of mutually supportive internal and external factors, especially the relevance of the collection and librarian services. Libraries need to strengthen their services, facilities, and literacy programs to increase student participation.